Which communities have better accessibility to green space? An investigation into environmental inequality using big data - Chen, Yang; Yue, Wenze; La Rosa, Daniele (Landscape and urban planning, 2020)
•A real-time navigation route measurement based on Amap application programming interface was developed to measure green space accessibility.•Central and peri-urban areas diverged in green space accessibility.•Within the inner and middle ring roads, the wealthier the communities, the better green space accessibility.•Shanghai’s spatial reconstructing affected the inequality of green space accessibility.•Inequality may be associated with gentrification process driven by greening strategies. Green space accessibility is widely acknowledged as a crucial aspect of a livable environment and human well-being. Whether green space accessibility is equitable among communities is increasingly considered as an issue of environmental justice. Therefore, this study focuses on the possible environmental inequality of green space accessibility that can be found among residential communities in the context of Chinese booming housing market. The case study of Shanghai, China was conducted with the use of big data. A real-time navigation route measurement based on Amap application programming interface (AAPI) was developed to calculate green space accessibility, and housing price was used to indicate dwellers’ socioeconomic status. Bivariate Moran’s I, multiple regression, and spatial lag regression were adopted to explore inequality of green space accessibility among residential communities. The results reveal a spatial inequality of green space accessibility between communities in central portion of the city and those in peri-urban areas. We further found a spatial mismatch between green space accessibility and housing price. Environmental inequality is evident within the inner and middle ring road wherein wealthier communities benefit more from green space accessibility than disadvantaged communities. We attribute these findings to spatial restructuring and green gentrification process in Shanghai. The findings can inform planners and policymakers to determine where and how to implement greening strategies and to gain awareness to prevent environmental inequality.